1998
DOI: 10.1006/jsre.1998.5403
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Preconditioning Ameliorates Liver Injury Following Normothermic Ischemia–Reperfusion in Steatotic Rat Livers

Abstract: The decreased tolerance of steatotic livers to warm ischemia complicates liver surgery. The efficacy of heat shock preconditioning in steatotic livers to lessen ischemia-reperfusion injury was studied in rats. Steatotic liver was produced in Lewis rats with a choline-deficient diet. Rats with steatotic livers were divided into a heat shock preconditioned group (group HS) and a control group (group C). All rats received 45 min of hepatic warm ischemia. Survival rates and changes in biochemical and histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…It has been similarly reported in the liver that ischemic or heat shock preconditioning exerts a protective effect on hepatic ischemia-reperfusion injury. [10][11][12][13][14][15][16][17][18]24 Although little is known about the molecular basis of the preconditioning, oxidative stress seems to be one of the causes. Peralta et al 15,25 and Yin et al 26 have reported the role of nitric oxide and free radicals during ischemic preconditioning in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been similarly reported in the liver that ischemic or heat shock preconditioning exerts a protective effect on hepatic ischemia-reperfusion injury. [10][11][12][13][14][15][16][17][18]24 Although little is known about the molecular basis of the preconditioning, oxidative stress seems to be one of the causes. Peralta et al 15,25 and Yin et al 26 have reported the role of nitric oxide and free radicals during ischemic preconditioning in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HSPs induced by the stresses may also play a critical role for the subsequent hepatic injury. [17][18][19] In Pringle' s maneuver in liver surgery and liver transplantation, the ischemia-reperfusion is an unavoidable process and the protection against liver damage induced by the operation is one of the major problems. Ischemia-reperfusion injury is considered to be related to the generation of free oxygen radicals, which is also implicated in the cellular response to several agents associated with pathophysiological and pathological stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recent studies have shown that the same phenomenon could also be observed in the liver. [4][5][6][7][8][9][10] In particular, 10-minute interruption of liver blood supply in anesthetized rats followed by 10 minutes of reperfusion reduces transaminases released during a subsequent 90-minute period of ischemia and 90-minute reoxygenation. 5 A similar effect has also been observed in steatosic livers following heat shock preconditioning.…”
mentioning
confidence: 99%
“…5 A similar effect has also been observed in steatosic livers following heat shock preconditioning. 7 Furthermore, ischemic preconditioning before cold preservation prevents reperfusion injury of liver endothelial cells 9 and increases rat survival after liver transplant. 6 Experiments performed using isolated hepatocyte suspensions show that the hepatoprotective action of liver preconditioning observed in vivo can be reproduced in vitro.…”
mentioning
confidence: 99%